The Effect of Brief Mindfulness Psychoeducation on the Emotional Regulation Ability of Coaching Students - Gedis Isnarizanah; Siti Nursaba (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to determine the effect of brief mindfulness psychoeducation on the emotional regulation abilities of sports coaching students. The background of this study is based on the importance of emotional regulation in the context of coaching education, where students are required to maintain emotional stability when facing academic pressure and interacting with athletes. This study uses a quasi-experimental design with a one-group pretest-posttest model. The research subjects consisted of 20 sports coaching students at the Indonesia University of Education, selected through purposive sampling. The instrument used was the Emotion Regulation Questionnaire (ERQ) to measure the aspects of cognitive reappraisal and expressive suppression. The intervention in the form of brief mindfulness psychoeducation was carried out over six sessions in three weeks, with material covering conscious breathing, light meditation, and awareness in daily activities. Data analysis used a paired sample t-test. The results showed a significant increase in cognitive reappraisal (p < 0.05) and a significant decrease in expressive suppression (p < 0.05). Thus, brief mindfulness psychoeducation proved effective in improving the emotional regulation of physical education students, particularly in their ability to reinterpret emotional situations and reduce the tendency to suppress emotional expression. This study provides practical recommendations for educational institutions to integrate mindfulness psychoeducation programs as part of the emotional competency development of student trainers.